Unravelling Breast Cancer Risks and Early Detection Barriers in Above 30-Year-Old Women in Puducherry, India - Sreya Prakash; Karthiga Vijayakumar; Kavita Vasudevan (National Journal of Community Medicine)
Background: Breast cancer is the leading cause of cancer death among women all over the world and one of the most treatable cancers if detected early. The objective was to find out the lifetime risk of developing breast cancer and various factors associated with its development, and to identify various barriers to early detection of breast cancer among women in Puducherry.